NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERPEN KONVENSI KARYA A. MUSTOFA BISRI - M. Yanuardi Zain; Supriyono Supriyono; Andri Wicaksono (LPPM STKIP PGRI Bandar Lampung, 2021)
This study aims to examine the values ​​of character education in a collection of convention short stories by A. Mustofa. The type of research used is descriptive qualitative method. This method is used to examine the values ​​of character education in the collection of short stories Convention by A. Mustofa Bisri. Qualitative methods pay attention to scientific data, data in relation to the context of their existence. Qualitative methods lead to data in the form of quote sentences that put forward words or sentences rather than numbers. Based on the results of the research that has been described regarding Character Education Values ​​in A. Mustofa's Convention Short Story Collection, it can be concluded that the character education values ​​in the Convention short story collection are classified as having 18 dominant character education values, namely; religious values, reading pleasure values ​​and attitudes and behavior values.